DEVELOPING LISTENING PROCEDURAL TEXT MATERIAL CONTAINING FUN ACTIVITIES The Case of the Eighth Graders of Junior High School To Strengthen the Character Education - Arumsari, Ina Rosita; Bharati, Dwi Anggani Linggar (Universitas Negeri Semarang, 2015)
The objective this study was to develop listening procedural text material containing fun activities. It was made for the eighth graders to strengthen character education. The design used in this study was Research and Development (R&D) proposed by Borg and Gall (1983: 775). The subject of this research was the eighth graders of Junior High School. The data would were analyzed through triangulation using three kinds of instruments, namely observation sheet, interview, and questionn1aire. The result of the data analysis is that the students gave the good opinions about the developed material. All of them liked the material very much. The results of assessments were very satisfying and student‘s attitude improvement ran smoothly. It showed that students‘ comprehension of procedure text was improving. It could be seen from the result of the post test. The eighth graders of SMP 1 Kudus got 97.03 for the average, while SMP 3 Bae Kudus could reach 95.32. The listening material containing fun activities called ―I Love How to Do‖ and the ―WhisbledWhizzle‖ game are completely good. This implies that developing listening of procedural material containing fun activities is effective for the eighth graders of junior high school.